The use and detection of quantum dots as nanotracers in environmental fate studies of engineered nanoparticles. (15th January 2023) - Pavlicek, Anna; Neubauer, Simon; Zafiu, Christian; Huber-Humer, Marion; Ehmoser, Eva-Kathrin; Part, Florian
Abstract: Investigations of the behavior and effects of engineered nanoparticles (ENPs) on human health and the environment need detailed knowledge of their fate and transport in environmental compartments. Such studies are highly challenging due to low environmental concentrations, varying size distribution of the particles and the interference with the natural background. A strategy to overcome these limits is to use mimics of ENPs with unique detectable properties that match the properties of the ENPs as nanotracers. A special class of ENPs that can be tracked are quantum dots (QDs). QDs are composed of different metals, metalloids, or more recently also carbon (e.g., graphene), that result in unique optical properties. This allows the tracking of such particles by fluorescence microscopic and photometric techniques. Many types of QDs consist of heavy elements, allowing to track and visualize these particles also by electron microscopy and to quantitate the particles indirectly based on these elements. QDs can also be surface modified in various ways which enable them to be used as a label or as traceable mimics for ENPs. This review reflects a broad range of methods to synthesize and modify QDs based on metals, metalloids, and graphene for studying the environmental fate of nanoparticles and discusses and compares analytical methods that can be used for tracking and quantifying QDs. In addition, we review applications of QDs as ENP mimics in environmental studies of surface waters, soils, microorganisms, and plants with respect to the applied analytical techniques.